Familial Hypercholesterolemia Prevalence Among Ethnicities—Systematic Review and Meta-Analysis - Toft-Nielsen, Frida; Emanuelsson, Frida; Benn, Marianne (Frontiers in Genetics, 2022)
Background Heterozygous familial hypercholesterolemia(FH) is a common genetic disorder leading to premature cardiovascular disease and death as a result of lifelong high plasma low-density lipoprotein cholesterol levels, if not treated early in life. The prevalence of FH varies be-tween countries because of founder effects, use of different diagnostic criteria, and screening strategies. However, little is known about differences in FH prevalence according to ethnici-ty. We aimed to investigate the ethnic distribution of FH in diverse populations and to esti-mate the prevalence of FH according to ethnicity. Methods We performed a systematic review and meta-analysis, searching PubMed and Web of Sci-ence for studies presenting data on prevalence of heterozygous FH among different ethnici-ties in non-founder populations. Studies with more than 100 individuals, relevant data on prevalence, ethnicity, and using the Dutch Lipid Clinical Network Criteria, Simon Broome, Making Early Diagnosis Prevents Early Death, genetic screening, or comparable diagnostic criteria were considered eligible for inclusion. Results Eleven general population studies and two patient studies were included in a systematic re-view and 11 general population studies in a random-effects meta-analysis. The overall pooled FH prevalence was 0.33% or 1:303 in 1,169,879 individuals(95% confidence interval: 0.26-0:40%; 1:385-1:250). Included studies presented data on six ethnicities: black, Latino, white, Asian, brown, and mixed/other. Pooled prevalence was estimated for each group. The highest prevalence observed was 0.52% or 1:192 among black(0.34-0.69%; 1:294-1:145) and 0.48% or 1:208 among brown(0.31-0.74%; 1:323-1:135), while the lowest pooled prevalence was 0.25% or 1:400 among Asian(0.15-0.35; 1:500-1:286).The prevalence was 0.37% or 1:270 among Latino(0.24-0.69%; 1:417-1:145), 0.31% or 1:323 among white(0.24-0.41%; 1:417-1:244) and 0.32% or 1:313 among mixed/other individuals(0.13-0.52%; 1:769 -1:192). Conclusion The estimated FH prevalence displays a variation across ethnicity, ranging from 0.25%(1:400) to 0.52%(1:192), with the highest prevalence seen among black and brown and the lowest among Asian individuals. The differences observed suggest that targeted screen-ing among subpopulations may increase the identification of cases and thus the opportunity for prevention.